(untitled) (International Journal of Physiotherapy, 2021)
Background: Friedreich’s ataxia is a progressive degenerative disorder caused by deficiency of the frataxin protein. Expanded GAA repeats in intron 1 of the FXN gene lead to its heterochromatinization and transcriptional silencing. Strategies being trialed to treat Friedreich’s ataxia include drugs that improve mitochondrial function and reduce oxidative injury. It has been shown that mesenchymal stem cell (MSC)-derived factors can restore cellular homeostasis and function to frataxin deficient cells. Case Summary: Here, we report three FRDA cases treated with four consecutive allogeneic transplantations of umbilical cord-derived MSCs with 30 days interval, upon per patient regulatory approvals for advanced cellular therapy. Outcome Measures: The cases were followed up after the treatment in means of the therapeutic effect of the cellular treatment by attenuating the neurological findings and gene expression parameters. Conclusions: Closely followed promising safety and efficacy outcomes demonstrated that the MSC treatment for FRDA might positively affect the clinical results caused by the defect in this genetic-based disease.